Facial preservation following extreme mummification: Shrunken heads. (May 2018) - Houlton, Tobias M.R.; Wilkinson, Caroline
Highlights: Skin defects, facial creases, hairline, and earlobe structures are best preserved. Features dependant on skeletal support are lost, e.g. cranial shape and jawline. Melanin depletion, epidermal degeneration, applied stains, alter skin colour. Infrared reflectography and ultraviolet fluorescence enables detection of tertiary hair follicle patterns. A method of post-mortem depiction for commercial shrunken heads is proposed. Abstract: Shrunken heads are a mummification phenomenon unique to South America. Ceremonial tsantsa are ritually reduced heads from enemy victims of the Shuar, Achuar, Awajún (Aguaruna), Wampís (Huambisa), and Candoshi-Shapra cultures. Commercial shrunken heads are comparatively modern and fraudulently produced for the curio-market, often using stolen bodies from hospital mortuaries and graves. To achieve shrinkage and desiccation, heads undergo skinning, simmering (in water) and drying. Considering the intensive treatments applied, this research aims to identify how the facial structure can alter and impact identification using post-mortem depiction. Sixty-five human shrunken heads were assessed: 6 ceremonial, 36 commercial, and 23 ambiguous. Investigations included manual inspection, multi-detector computerised tomography, infrared reflectography, ultraviolet fluorescence and microscopic hair analysis. The mummification process disfigures the outer face, cheeks, nasal root and bridge form, including brow ridge, eyes, ears, mouth, and nose projection. Melanin depletion, epidermal degeneration, and any applied staining changes the natural skin complexion. Papillary and reticular dermis separation is possible. Normal hair structure (cuticle, cortex, medulla) is retained. Hair appears longer (unless cut) and more profuse following shrinkage. Significant features retained include skin defects, facial creases, hairlines and earlobe form. Hair conditions that only affect living scalps are preserved (e.g. nits, hair casts). Ear and nose cartilage helps to retain some morphological information. Commercial heads appear less distorted than ceremonial tsantsa, often presenting a definable eyebrow shape, vermillion lip shape, lip thickness (if mouth is open), philtrum form, and palpebral slit angle. Facial identification capabilities are considered limited, and only perceived possible for commercial heads.